Study and Analysis of UFMC Technology in 5G Communications - Vaigandla, Karthik Kumar; Siluveru, Mounika (IRO Journal on Sustainable Wireless Systems, 2023)
Wireless communication technology plays a significant role in the development of mobile technology. Every user requires their own spectrum. However, spectrum bands are limited. Therefore, the communication system must be efficient. This paper discusses the Universal Filtered Multi-Carrier (UFMC) technology, a new promising technology intended to improve mobile networks in the future. This technology is less susceptible to estimate errors of time shifts and frequency shifts. 5G’s major goals are speed, low latency, Quality of Service, and channel capacity. Physical layer waveform generation must be flexible in order to meet these requirements. Currently, 4G-LTE transmissions are not compatible with 5G technologies because of Out of Band radiation and high Peak to Average Power Ratio (PAPR). A future cellular network could benefit from UFMC. The performance of UFMC is evaluated using Power Spectral Density, PAPR, Signal-to-Noise Ratio, and Bit Error Ratio for 5G wireless communications. It is possible that UFMC will be more efficient and gives better solution.